(untitled) (Revista Sistemas de Producción Agroecológicos, 2014)
This work is part of project Production Optimization System beef and dairy cattle, in the eastern plains tropical zone of Colombia, the aim was to contribute to the use of colostrum, determining their immune quality in bovine females dual-purpose production in an area of the Llanos Foothills and establish the best method of preservation for strategic use in the first hours of life of the calf. For this differentiated quantification of immunoglobulin (Ig) concentrations in colostrum was performed up to 10 hours postpartum to establish the degree of association being the physical, chemical and immunological variables in colostrum. Four methods of preservation of colostrum for use on farms were also evaluated. The concentration of total Ig Media was 6,923 mg/dL. The average values ​​for each class of Ig were IgG: 5882 mg/dL. IgG1: 5544 mg/dL. IgG2: 338 mg/dL. IgM 670 mg/dL. IgA: 370 mg/dL. The average density was 1.057 mg/ml, 23.8 g/100 g dry matter and protein colostrum 13.3 g/100 g colostrum. The overall average for gamma glutmyl transferase (GGT) and milk fat was 730 IU/L of serum of colostrum and 3.78 g/100 g colostrum, respectively. These two variables had coefficients of variation higher. The average pH was 5.95, the average ash was 1.48 g/100 g of colostrum and Absorbance was 1.07%. A positive correlation (P<0.01) was found with density concentration of total Ig, IgG2, dry matter, total protein, ash, and GGT. Similarly dry matter is correlated with total protein and GGT (P<0.01) and total protein with ash (P<0.01) but to perform the function of the model is not adjusted dependence. However, it must perform additional similar studies since adjusting said international studies have reported a higher value in the dependency function at least in the case of the concentration of total Ig as a function of the density of the colostrum. The colostrum collected from two farms in this study demonstrated an immunological value of 6923 mg/dL, a value that is within those reported by other studies in temperate dairy specialist.